2022
DOI: 10.1038/s41467-022-30522-1
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-confined subnanometric PtSn mimicking mortise-and-tenon joinery for catalytic propane dehydrogenation

Abstract: Heterogeneous catalysts are often composite materials synthesized via several steps of chemical transformation, and thus the atomic structure in composite is a black-box. Herein with machine-learning-based atomic simulation we explore millions of structures for MFI zeolite encapsulated PtSn catalyst, demonstrating that the machine-learning enhanced large-scale potential energy surface scan offers a unique route to connect the thermodynamics and kinetics within catalysts’ preparation procedure. The functionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…In contrast, Ni n /Al 2 O 3 deactivates quickly, giving a high k d value of 0.427 h –1 . These results indicate that the catalytic performance of the Ni 1 /Al 2 O 3 catalyst can be completely recovered after the regeneration of the catalyst, and this remarkable stability of the Ni 1 /Al 2 O 3 catalyst for propane dehydrogenation is comparable to the reported Pt-based alloy catalysts. ,,, …”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast, Ni n /Al 2 O 3 deactivates quickly, giving a high k d value of 0.427 h –1 . These results indicate that the catalytic performance of the Ni 1 /Al 2 O 3 catalyst can be completely recovered after the regeneration of the catalyst, and this remarkable stability of the Ni 1 /Al 2 O 3 catalyst for propane dehydrogenation is comparable to the reported Pt-based alloy catalysts. ,,, …”
Section: Resultssupporting
confidence: 56%
“…Theoretical calculations and experimental tests have demonstrated that decreasing the Pt particle size to atomically dispersed atoms can significantly improve the turnover frequency of alkane dehydrogenation reactions while maintaining superior propylene selectivity and catalytic stability. Thus, synthesis of isolated metal sites through alloy formation has emerged as a practical strategy to inhibit undesired side reactions and enhance dehydrogenation performance of catalysts. For instance, promoter addition, such as Sn, Zn, Ce, Ga, Cu, and so forth, leads to higher olefin selectivity and lower coke formation by isolation of Pt atoms in ordered bimetallic alloy structures and adjusting the energy of the Pt valence orbitals. Another approach is the development of supported single-site catalysts, including Co 2+ , Zn 2+ , Sn 2+ , and Ga 3+ . Such metal-O-support sites provide an appropriate barrier for C–H activation and facilitate propylene desorption to inhibit the formation of coke, showing potential for next-generation PDH catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a promoter metal can facilitate the construction of FECCs. For example, a promoter can regulate the coordination environment of Pt atoms and modify its electronic property to optimize the adsorption/desorption behavior of FECCs. For stabilized FECCs, their structure dependence and metal dependence have been the thematic topics of heterogeneous catalysis in recent years. The development of modern synthetic techniques allows metal species dispersed on the support with a relatively narrow size distribution. Aided by advanced characterization tools and theoretical models, the catalytic performance can be correlated with metal cluster size and composition, to provide fundamental insights into catalytic dehydrogenation processes and, thus, the guideline for catalyst design.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 However, high temperatures (>550 °C) are always required since the reaction is endothermic, and this always triggers coke deposit formation and further leads to the deactivation of the catalyst. 7–9 Besides, CrO x and Pt catalysts are still commonly used in the industrial DHP reaction although they are toxic or expensive. 10 Oxidative dehydrogenation of propane (ODHP) 11–13 is also an important strategy to realize a highly efficient conversion of propane.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports on thermal catalytic CO 2 -ODHP, we found that CO 2 could be reduced to CO via a reverse water gas shift (RWGS) reaction. 7,9 In general, it is widely accepted that CO 2 plays a very important role in removing in situ formed H 2 and further shifts the reaction equilibrium to produce more propylene. However, in these reactions, the exact roles of CO 2 , especially how CO 2 promotes the working of the catalyst, is still unclear and is also a difficult task at present.…”
Section: Introductionmentioning
confidence: 99%